Microbiological solid state fermentation of apple pomace by yeast and fungus : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Biotechnology at Massey University, Palmerston North, New Zealand - Rahmat, Hishamudin (Massey University, 1991)
The enrichment of apple pomace prepared by the mechanical juice extraction process using Candida utilis Y15 was demonstrated. The organic protein content increased from 4.80% to 6.51% per dry weight of apple pomace with near total exhaustion of reducing sugar available. Using regression equation based on crude fibre content of the fermented apple pomace, the pomace may be more suitable as a feed for ruminants than for monogastrics animals. The citric acid production by Aspergillus niger NRRL 328 on apple pomace prepared by the enzymatic juice extraction process was also demonstrated. Aspergillus niger NRRL 328 was found to produce limited amounts of citric acid. Additions of three percent methanol (v/w) stimulated citric acid production significantly. Highest level of citric acid production was observed with addition of 4% (v/w) oil and 3% methanol, which was approximately 44% of the sugar consumed. The production of citric acid seemed to be nitrogen limiting. No citric acid was produced with any exogenous nitrogen addition. The optimum inoculum size was found to be 1 x 105 to 1 x 106 spores per 20 gram of apple pomace.
Keywords: Apples -- Processing; Apples -- By-products; Apples -- Biotechnology